Effectiveness of a Student-Centered Learning Approach in Improving Academic Achievement - M. Munif; Muh Habibulloh; Jhon Emily Stuart; Siti Fatinnah binti Ab Rahman (Journal of Education and Learning Sciences, 2025)
This study aims to analyze the effectiveness of the student-centered learning approach in improving academic achievement in elementary schools in Jombang Regency. The research employs a qualitative method with a descriptive approach. Data were collected through observations, interviews, and documentation involving students and teachers participating in the learning process. The findings indicate that the student-centered learning approach significantly contributes to enhancing students' understanding and academic performance. Students engaged in this method were more active, highly motivated, and demonstrated improvements in critical thinking and problem-solving skills. Teachers also experienced positive impacts in increasing student participation, although they faced challenges such as time constraints and the need to adapt teaching methods. The study concludes that student-centered learning can be an effective strategy for improving the quality of education in elementary schools. To ensure its success, support from various stakeholders is needed, including teacher training and the provision of adequate learning resources.